1134 A comparison of the aerogen vibrating mesh nebuliser versus a standard jet nebuliser to deliver bronchodilators in moderate to severe asthma in the emergency department. Issue 3 (21st February 2022) - Abdalla, Mohamed; ElKhodiar, Samer; Perez, Fabiola Sevilla; Wong, Rebecca; Austin, Helena; Rau, Clovis; Patterson, Michael; Garcia, Bobby; Leal, Tania; Murphy, Ciara; Ceris, Tuckey; Walton, Harriet
Abstract : Aims/Objectives/Background: Nebulised bronchodilators provide effective therapy for patients with Asthma. We sought to investigate the effectiveness of vibrating mesh nebuliser(VMN) when compared to a standard jet nebuliser(JN) in patients with moderate-to-severe asthma presenting to the Emergency Department (ED). we compared time to discharge from ED, drug delivery, and rate admission when using VMN technology compared to the JN. Methods/Design: A prospective, single-centre, non-blinded study comparing the efficacy of the VMN (Aerogen Solo) against the current standard jet nebuliser (JN)(Cirrus2 Nebuliser) to deliver nebulised Salbutamol (2.5 mg) in moderate to severe adult asthma within the ED. Patients requiring bronchodilator therapy were allocated for each arm to receive medications via the VMN, or by standard JN. Patients were managed by emergency physicians according to the joint BTS guidance. The primary endpoint was time to discharge from ED (mins) after initial physician assessment, while among the secondary endpoints examined were Salbutamol dose (mg), and rate of discharge from ED (binary). Time to discharge & salbutamol dose were summarized via the Median (IQR), and a nonparametric Mann-Whitney U test was applied to derive a p-value for the comparison. The mean (SD) was also tabulated. The rate of admission for each arm was calculated, and compared using a chi-squared test. Results/Conclusions: 124 patients completed the study. Time to discharge and salbutamol dose, were significantly lower in those patients treated with VMN showing a statistical significance (p=0.003 and p=0.023 respectively).VMN time to discharge: Mean (SD) 136.44 mins (89.50). VMN salbutamol dose 7.58 mg; In comparison to those treated in the JN arm. JN time to discharge: Mean (SD) 175.31 mins (97.15) JN salbutamol: 9.69 mg. No Statistical Significance for the rate of admission. Treatment with a VMN led to a significant reduction in both the median length of stay and the requirement for bronchodilators in the ED.